PENGENALAN ASAP CAIR DARI HASIL PIROLISIS TEMPURUNG KELAPA SEBAGAI PENGAWET TAHU DI GAPOKTAN SABOLIO SUNGAI DUA BANYUASIN - Ade Oktasari; Fitria Wijayanti; Riska Ahsanunnisa; Susi Arianti (Politeknik Negeri Sriwijaya, 2023)
Banyuasin is the largest coconut producing area in South Sumatra, but the coconut waste has not been utilized properly by the community. The introduction of liquid as soon as possible to the Sabolio farmer group aims to provide education to the public regarding alternatives to processing coconut shell waste into tofu preservatives which will have a sale value in the community. This counseling was carried out based on a questionnaire that had been given to the public regarding the use of food preservatives, especially tofu. So far, people only use natural preservatives in the form of salt which only lasts a short time without using a refrigerator. Therefore, a natural preservative product is produced to be able to extend the shelf life of tofu outdoors. Visits in community service were carried out three times attended by 22 peoples, the majority of which were attended by mothers.